Meta‐analysis of the impact of successful chronic total occlusion percutaneous coronary intervention on left ventricular systolic function and reverse remodeling. (4th July 2018) - Megaly, Michael; Saad, Marwan; Tajti, Peter; Burke, M. Nicholas; Chavez, Ivan; Gössl, Mario; Lips, Daniel; Mooney, Michael; Poulose, Anil; Sorajja, Paul; Traverse, Jay; Wang, Yale; et al.
Abstract : Background: We sought to examine the impact of coronary chronic total occlusion (CTO) percutaneous coronary intervention (PCI) on left ventricular (LV) function. Methods: We performed a systematic review and meta‐analysis of studies published between January 1980 and November 2017 on the impact of successful CTO PCI on LV function. Results: A total of 34 observational studies including 2735 patients were included in the meta‐analysis. Over a weighted mean follow‐up of 7.9 months, successful CTO PCI was associated with an increase in LV ejection fraction by 3.8% (95%CI 3.0‐4.7, P  < 0.0001, I 2  = 45%). In secondary analysis of 15 studies (1248 patients) that defined CTOs as occlusions of at least 3‐month duration and reported follow‐up of at least 3‐months after the procedure, successful CTO PCI was associated with improvement in LV ejection fraction by 4.3% (95%CI [3.1, 5.6], P  < 0.0001). In the 10 studies (502 patients) that reported LV end‐systolic volume, successful CTO PCI was associated with a decrease in LV end‐systolic volume by 4 mL, (95%CI −6.0 to −2.1, P  < 0.0001, I 2  = 0%). LV end‐diastolic volume was reported in 9 studies with 403 patients and did not significantly change after successful CTO PCI (−2.3 mL, 95%CI −5.7 to 1.2 mL, P  = 0.19, I 2  = 0%). Conclusions: Successful CTO PCI is associated with a statistically significant improvement in LV ejection fraction and decrease in LV end‐systolic volume, that may reflect a beneficial effect of CTO recanalization on LV remodeling. The clinical implications of these findings warrant further investigation.